2017
DOI: 10.1136/annrheumdis-2016-210708
|View full text |Cite
|
Sign up to set email alerts
|

Safety of synthetic and biological DMARDs: a systematic literature review informing the 2016 update of the EULAR recommendations for management of rheumatoid arthritis

Abstract: ObjectivesTo assess the safety of synthetic (s) and biological (b) disease-modifying antirheumatic drugs (DMARDs) for the management of rheumatoid arthritis (RA) to inform the European League Against Rheumatism recommendations for the management of RA.MethodsSystematic literature review (SLR) of observational studies comparing any DMARD with another intervention for the management of patients with RA. All safety outcomes were included. A comparator group was required for the study to be included. Risk of bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
214
3
17

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(237 citation statements)
references
References 65 publications
3
214
3
17
Order By: Relevance
“…The selected group of patients included in RCTs as well as the relatively short duration of RCTs, makes addressing long-term safety of drugs in RCTs difficult. For this reason, safety aspects of GCs and csDMARDs were addressed in a separate SLR based on observational studies coming from registries 5. Some safety issues regarding tsDMARDs will be discussed here, since real life data of tsDMARDs are still lacking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected group of patients included in RCTs as well as the relatively short duration of RCTs, makes addressing long-term safety of drugs in RCTs difficult. For this reason, safety aspects of GCs and csDMARDs were addressed in a separate SLR based on observational studies coming from registries 5. Some safety issues regarding tsDMARDs will be discussed here, since real life data of tsDMARDs are still lacking.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this and two other systematic literature reviews (SLRs)4 5 provided the task force with the current state of evidence.…”
Section: Introductionmentioning
confidence: 97%
“…54 For example, results from a metaanalysis showed that adults with RA had a higher risk of serious infections, tuberculosis and melanoma when receiving biologic DMARDS as compared to conven tional DMARDS. 55 These findings call for a change in treatment strategies in paediatric rheumatology, and in JIA in particular. The proposal of consensus treatment plans by CARRA for newonset systemic JIA and pro liferative arthritis in juvenile SLE has been suggested as a starting point to address some of these concerns.…”
Section: Clinical Trials In Jiamentioning
confidence: 97%
“…Обсуждение РТМ в комбинации с МТ рассматривается как эффе-ктивный и относительно безопасный метод лечения РА в рамках современной стратегии лечения РА («Лечение до достижения цели»; Treat to Target), который не уступает по эффективности комбинированной терапии БПВП с други-ми ГИБП [10,17,22]. Однако показания к назначению РТМ при РА и выбор оптимальных доз препарата для ин-дукционной и поддерживающей терапии являются пред-метом дискуссий [33,34], что стимулирует дальнейшие ис-следования в этом направлении [35].…”
Section: таблицаunclassified
“…Детальная характеристика меха-низмов действия РТМ и последствий «депле-ции» В-клеток при РА детально обсуждены в наших предыдущих публикациях [10,12], обзорах других авторов [13,14]. Эффектив-ность и безопасность РТМ как у пациентов с развернутым РА, резистентных к базисным противовоспалительным препаратам (БПВП) и ингибиторам ФНОα, так и у пациентов с ранним РА в качестве «первого» генно-ин-женерного биологического препарата (ГИБП) подтверждена в многочисленных широкомасштабных рандомизированных плацебоконтролируемых исследованиях (РПКИ), материалы которых суммированы в обзорах [10][11][12], их метаанализах [15][16][17], а также данными реальной клинической пра-ктики в рамках наблюдательных исследова-ний и национальных регистров [18][19][20][21]. Это позволило рассматривать РТМ как высокоэф-фективный ГИБП и рекомендовать его для лечения РА у пациентов, резистентных к ме-тотрексату (МТ) и другим БПВП при недоста-точной эффективности предшествующей те-рапии другими ГИБП, в первую очередь ин-гибиторами ФНОα [22][23][24], и, при опреде-ленных показаниях, «первым» ГИБП.…”
unclassified